Model manajemen Madrasah Aliyah Pembangunan Universitas Islam Negeri (UIN) Jakarta - Achmad Widodo, Syukri Fathudin; Sudrajat, Ajat; Sugiyono, Sugiyono (Universitas Negeri Yogyakarta, 2020)
The article aims to see the Management Model of Madrasah Aliyah Laboratorium from the aspects of planning, organizing, implementing, and monitoring. At Madrasah Aliyah Pembangunan (MAP) UIN Jakarta. The research method used is qualitative. The results showed the Madrasah Aliyah Laboratory management model consists of the first three components: the organizational structure of the Madrasah Aliyah Laboratory, including management (Director) and Madrasah Implementer (Madrasah Head), the second existing culture (culture). in Madrasah Aliyah Laboratory including academic and non-academic including custom curriculum, reading habits, English-Arabic days and the three figures who play a role in Madrasah Aliyah Laboratorium, both head of a madrasah, teachers, and madrasah committee